2022
DOI: 10.1155/2022/1802707
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Accuracy of qSOFA and SIRS for Mortality in the Emergency Department: A Meta-Analysis and Systematic Review of Prospective Studies

Abstract: Objective. This meta-analysis aimed to determine the prognostic performance of quick sequential organ failure assessment (qSOFA) score in comparison to systemic inflammatory response syndrome (SIRS) in predicting in-hospital mortality in the emergency department (ED) patients. Methods. Eligible studies comparing the performance of qSOFA and SIRS in predicting in-hospital death of ED patients were identified from searching PubMed, Embase, and Cochrane. Raw data were collected, and the pooled sensitivity and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The performance of qSOFA has been controversial with varying results in different studies. In our study, we found an AUC of 0.61 of qSOFA on 30-day mortality, which is considered too low to reliably predict mortality in the ED [ 7 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 97%
“…The performance of qSOFA has been controversial with varying results in different studies. In our study, we found an AUC of 0.61 of qSOFA on 30-day mortality, which is considered too low to reliably predict mortality in the ED [ 7 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 97%
“…Many studies showed that qSOFA has a low sensitivity but high specificity when it is used in ED for predicting mortality. The low sensitivity made the use of qSOFA alone could not satisfy clinicians, especially when it is used in ED for predicting mortality (16,18). A study in patients with secondary peritonitis showed that qSOFA's predictive performance for inhospital mortality has been found to be inferior to SIRS criteria (12).…”
Section: Discussionmentioning
confidence: 99%
“…The net reclassification index, integrated discrimination improvement and decision curve analysis are the previous three statistical methods that are currently frequently utilised to evaluate prediction models. 4 However, the AUC analysis is the only method used in this paper.…”
mentioning
confidence: 99%
“…A recent meta-analysis of 16 prospective studies found qSOFA to have a pooled AUC of 0.76 (0.72-0.8) for in-hospital mortality. 4 A systematic review and meta-analysis of 24 studies (23 using qSOFA) found the pooled AUC for qSOFA for mortality to be 0.77 (0.72-0.82). 5 Individual studies with an AUC for qSOFA for predicting 28-day mortality higher than 0.8 include that by Quinten et al, which found qSOFA to have an AUC of 0.85 (0.73-0.96), 6 and Boillat-Blanco et al, with an AUC of 0.8 (0.73-0.87).…”
mentioning
confidence: 99%